Analysis of secular variations of geomagnetic field in Lithuania based on the survey in 2016 - Būga, Arūnas; Einorytė, Simona; Obuchovski, Romuald; Puškorius, Vytautas; Petroškevičius, Petras (International Conference “Environmental Engineering”, 2017)
Lithuania is successfully integrated in the European geomagnetic field research activities. Six secular variation research stations were established in 1999 and precise geomagnetic field measurements were performed there in 1999, 2001, 2004, 2007 and 2016. Obtained diurnal magnetic field variations at measuring station and neighbouring observatories were analysed. All measurements are reduced to the mean of the year using data from geomagnetic observatory of Belsk. Based on the measured data the analysis of geomagnetic field parameter secular changes was performed. Results of the presented re search are useful for updating the old geomagnetic data as well as for estimation of accuracy of declination model.
Keywords: geomagnetic field; geomagnetic field secular variations; repeat stations